A new type of novel salt-inclusion chalcogenide with ultralow thermal conductivity. Issue 96 (19th November 2020) - Chen, Hong; Liu, Peng-Fei; Lin, Hua; Wu, Xin-Tao
Abstract : A new type of salt-inclusion chalcogenide, [Rb6 Cl][RE23 Mn7 Se44 ] (RE = Ho–Yb), with a unique host–guest structure that exhibits ultralow thermal conductivity is demonstrated. Abstract : The design and development of novel chalcogenides with ultralow thermal conductivity is extremely important but very challenging for promoting the efficiencies of thermoelectric (TE) materials. Herein, a new type of salt-inclusion chalcogenide (SIC), [Rb6 Cl][RE23 Mn7 Se44 ] (RE = Ho–Yb), was discovered via a modified flux method. They possessed [RESe6 ] and [MSe6 ] (M = RE/Mn) octahedra as basic building units, which interlinked to form a three-dimensional quasi-NaCl-type [RE23 Mn7 Se44 ] 5− host framework, where the [Rb6 Cl] 5+ guest ions resided. Interestingly, these isomorphic compounds showed ultralow thermal conductivities (0.28–0.37 W m −1 K −1 ) at 673 K, which are reported for the first time in SICs. This work not only enriches SIC chemistry but also broadens the application of SICs in the TE field.